Is a Preoperative Gastrointestinal Endoscopy for Second Primary Cancer Detection in Head and Neck Cancer Necessary? Ten-year Registry Data - Gyeong Mi Heo; Mi Hee Kim; Jin Hwan Kim; Young Soo Rho; Woon Geon Shin (The Korean Journal of Gastroenterology, 2016)
Background : /Aims: In head and neck squamous cell carcinoma, second primary gastrointestinal tumors are not uncommon. However, it is unclear whether a screening endoscopy is needed for detecting gastrointestinal neoplasm in patients with head and neck cancer. Therefore, we analyzed the prevalence and independent risk factors for second primary gastrointestinal neoplasm in head and neck squamous cell carcinoma. Methods : : A consecutive series of 328 patients with primary head and neck squamous cell carcinoma that underwent esophagogas-troduodenoscopy or colonoscopy were included using our registry. An age- and sex-matched group of 328 control subjects was enrolled. We assessed risk factors of synchronous gastrointestinal cancer. Results : : The prevalence of esophageal cancer with head and neck squamous cell carcinoma was significantly higher than that of the control group (1.5% vs. 0.0%, p=0.011). An age of 54 years or more (OR, 1.033; 95% CI, 1.008-1.059; p=0.009) and male gender (OR, 4.974; 95% CI, 1.648-15.013; p=0.004) were risk factors for concomitant colorectal cancer or adenomas in the head and neck squamous cell carcinoma patients. Conclusion : s: Preoperative colonoscopy can be recommended for detecting synchronous second primary colorectal lesions in head and neck squamous cell carcinoma patients with male sex regardless of age, and esophagogastroduodenoscopy is necessary in all head and neck squamous cell carcinoma patients for detecting esophageal cancer. (Korean J Gastroenterol 2016;68:23-28)